Aristotle : a very short introduction - Barnes, Jonathan, 1942- (Oxford ; New York : Oxford University Press, 2000)
""Jonathan Barnes examines Aristotle's scientific researches, his discoveries in logic and his metaphysical theories, his work in psychology and in ethics and politics, and his ideas about art and poetry, placing his teachings in their historical context.""--Publisher description
The man and his work -- A public figure -- Zoological researches -- Collecting facts -- The philosophical background -- The structure of the sciences -- Logic -- Knowledge -- Ideal and achievement -- Reality -- Change -- Causes -- Empiricism -- Aristotle's world-picture -- Psychology -- Evidence and theory -- Teleology -- Practical philosophy -- The arts -- Afterlife -- Chronological table
Includes bibliographical references (pages 153-156) and index
Keywords: Aristotle